Penerapan Perawatan Nesting terhadap Pencegahan Hipotermi pada Bayi Berat Lahir Rendah (BBLR) di Ruang Perinatologi - Rotua Marline Tambunan; Srimiyati Srimiyati; Ketut Suryani (STIKES Columbia Asia Medan, 2026)
Low Birth Weight (LBW) infants are a group of neonates who are highly susceptible to thermoregulation disorders, particularly hypothermia, due to limited subcutaneous fat reserves, a relatively large body surface area, and the immaturity of the temperature regulation system. Untreated hypothermia can lead to serious complications such as hypoxia, sepsis, hypoglycemia, apnea, and failure to gain weight, which ultimately contribute to increased neonatal morbidity and mortality. One of the non-pharmacological nursing interventions that can be used to prevent hypothermia is nesting care, a positioning technique using supportive materials to create a comfortable environment that resembles the intrauterine position.This study aimed to determine the effectiveness of nesting care in LBW infants as an effort to increase body temperature in infants experiencing hypothermia. The method used was a descriptive case study with a nursing process approach involving three participants. The intervention consisted of nesting care administered for three days, with a duration of 30 minutes once daily using the quarter-prone or semi-prone position. The results showed that after the nesting intervention, two out of three participants experienced an increase in body temperature approaching normal values on the third day. Improvement in the infants' condition was also indicated by reduced crying and longer periods of calm sleep compared to the condition before the intervention. Body temperature measurements and observations of the infants’ condition were conducted periodically to evaluate the effectiveness of the intervention, with an average temperature increase of approximately 0.2°C at the end of the intervention. In conclusion, nesting care can be used as an effective non-pharmacological nursing intervention to help increase body temperature in LBW infants experiencing hypothermia.